Performance of Oreochromis niloticus juveniles fed autoclaved mango seed kernel diets - Falaye Augustine Eyiwunmi; Sule Okanlawon Shakiru; Sanogo Salimata; Kechicha Olufunmike Martha (Syiah Kuala University, 2021)
Human and livestock population increase has led to escalating prices of energy feed stuffs used in aquaculture. There have been some researches on various inexpensive agro-industrial by-products as substitutes for maize in fish diets with varying degrees of success. This study investigated the growth performance of Oreochromis niloticus juveniles fed with autoclaved Mango seed formulated fish diet as a dietary energy source at different inclusion level. 150 Oreochromis niloticus juveniles with mean weight of 10.24±0.05g were randomly allocated to five dietary treatments (T1, T2, T3, T4, T5). The fish were acclimated for two weeks and were allotted to five treatments in plastic tanks (26x46x20cm). Each treatment contained 10 fish per tank. The fish were fed experimental diets at T1:0%, T2: 25%, T3: 50%, T4: 75% and T5: 100% Mango Seed Kernel Meal (MSKM) inclusion levels respectively. The highest Mean weight Gain (MWG) and lowest Feed Conversion Ratio (FCR) was recorded in Treatment 2: 25% (48.93±4.88); (0.91±0.07) while the lowest MWG and highest FCR was recorded in Treatment 5: 100% (27.30±3.99); (1.47±0.16). Specific Growth Rate (SGR) was lower in Treatment 5: 100% when compared to other treatments. Feed intake followed a decreasing order. The blood samples collected showed that there was significant differences (p0.05) In conclusion, growth performance and haematological activity could be best improved by substituting mango seed kernel meal at 75% with no implication on growth and fish health.